2008
DOI: 10.1108/09699980810902721
|View full text |Cite
|
Sign up to set email alerts
|

Flow modelling of construction site materials and waste logistics

Abstract: PurposeThe purpose of this paper is to determine the nature and extent of the current practice of logistics in the construction industry and to investigate the utility of reverse logistics in a construction context.Design/methodology/approachA pilot study was utilised to devise a method for the identification and measurement of parameters for incorporation within a process of construction site logistics optimisation. Data on vehicular movements were collected from seven sites in Cape Town. The data were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 13 publications
1
20
2
Order By: Relevance
“…The field observation established that significant amount of materials delivery vehicle movements (more than 45%) were empty runs to their return journey and 35% of C&D waste removal vehicle movements were empty runs on their forward journey. Compare to the similar study carried out in South Africa (Shakantu et al, 2008), it appears that the ratio at the observed site is higher than the counterparts in SA. During the construction process, some of the waste removal companies arrived site with empty bins and exchanged the filled bins back to either the landfills or company recycle plants.…”
Section: Truck Movement Patternscontrasting
confidence: 86%
See 2 more Smart Citations
“…The field observation established that significant amount of materials delivery vehicle movements (more than 45%) were empty runs to their return journey and 35% of C&D waste removal vehicle movements were empty runs on their forward journey. Compare to the similar study carried out in South Africa (Shakantu et al, 2008), it appears that the ratio at the observed site is higher than the counterparts in SA. During the construction process, some of the waste removal companies arrived site with empty bins and exchanged the filled bins back to either the landfills or company recycle plants.…”
Section: Truck Movement Patternscontrasting
confidence: 86%
“…From the non-monetary aspects, high transport requirement results in high social costs as well as a wide range of associated negative environmental impacts in the form of congestion, road accidents, environmental pollution, and noise generation (Shakantu et al, 2008).…”
Section: Awareness Of Logistics Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the results of the content analysis indicated that the current focus of reverse logistics literature in the construction industry is primarily on end-of-life waste management. Hosseini et al [17] x Chileshe et al [18] x Hosseini et al [19] x Chileshe et al [25] x Nunes et al [26] x Arif et al [27] x Aidonis et al [30] x Aidonis et al [31] x Al-Aomar and Weriakat [32] x Arif et al [33] x Beldek et al [34] x Bock and Linner [35] x Bock and Linner, [36] x Chileshe, et al [37] x x Chinda [38] x Chinda and Ammarapala [39] x Chinda et al [40] x Dim et al [41] x Ding et al [42] x Fabbe-Costes and Jahre [43] x Fu et al [44] x Gomes et al [45] x Hosseini et al [46] x Ketikidis et al [47] x Kim et al [48] x Mathiyazhagan and Noorul [49] x x Negi et al [50] x Netro et al [51] x Ojo et al [52] x Ojo et al [53] x Qiuliang et al [54] x Rameezdeen et al [55] x Sabai [56] x Schamne et al [57] x Schultmann and Sunke [58] x Shakantu, and Emuze [59] x Shakantu et al [60] x Simon et al [61] x Sinha and Taneerananon [62] x Sobotka and Czaja [63] x Sobotka and Segan [64] x Stokić and Rado...…”
Section: Focus Of Reverse Logisticsmentioning
confidence: 99%
“…An inverse logistics and recycling facilities network evaluation system was developed and applied to collecting and recycling municipal waste plastics by means of simulation and virtual engineering by Yoshinaga et al (2002). Further outside retail domain construction site material and waste flow was modelled and examined (Shakantu et al 2008), while Hogland and Stenis (2000) conducted an assessment and analysis of an industrial WMS at a large paper company and Abeliotis et al (2009) developed a decision support system for analysing solid WMS on national and municipal level. Methodologically, European Commission Directorate-General Environment (EC DGE 2012) proposes a WM planning guidance and UNEP (2009) sets forth basic analytical perspectives on WMS.…”
Section: Literature Reviewmentioning
confidence: 99%